ANALISIS PERTUMBUHAN TABUNGAN ANGGOTA PADA KOPERASI KREDIT CREDIT UNION KHATULISTIWA BAKTI KALIMANTAN BARAT - B21111021, Agusandi (Jurnal Pembangunan dan Pemerataan, 2015)
This study entitled "Analysis of Growth Savings Credit Koperasi Credit Union West Kalimantan Bakti Khatulistiwa". Credit Koperasi Credit Union Khatulistiwa Bakti is a financial institution that serves to collect public savings, investment financing channel for its members. The number of members and total assets increased from year 2009-2013 shows that the growth of public interest in saving. The objective of this research was to determine and analyze the growth of private savings, identify the obstacles faced and know the effort that has been made in improving the members' savings.The sampling method used in this research is descriptive which describes the circumstances of what happened in the field by using a qualitative analysis of questionnaires submitted to the respondent then summed and presented recently analyzed which data are available.From the data analysis, the percentage of this research note that people's incomes, interest rates and affect members saving products. Constraints in raising public funds lack of field staff, freight transport streams that do not support and the lack of dissemination to members. efforts made to increase public savings held continuous basic education, promotion, improve service, hire collectors, doing business group produktf economy, provide compensation and insurance, Access Branding.Keywords: Growth Savings